Profitabilitas Hedging Dalam Transaksi Valuta Asing (Studi Kasus PT. BZI, Jawa Barat Dalam Periode April 2021 – September 2024) - Setyo Wardhana, Tri; Albart, Nicko (Journal of Accounting and Finance Management, 2024)
Hedging is a financial policy which is implemented with the purpose of minimizing the risk of transaction exposure due to the fluctuation of foreign exchange. This research aims to investigate the profitability of hedging activity done by PT. BZI using a derivative instrument in the form of forward contract during the period of April 2021 to September 2024. This research is quantitative descriptive research with case study approach, which calculated the hedging profitability by multiply the hedging amount with the difference value between forward contract rate with the spot rate (telegraphic transfer selling rate) on the maturity date of transaction to from the same bank that has provided the hedging facility. From the research results, it is known that 23 of the 34 forward contract transactions carried out by PT.BZI during above mentioned period had achieved the purpose of hedging. Even though 11 of the 34 forward contract transactions showed a negative result calculation, the accumulated result was still in positive value, which means that the purpose of hedging was well achieved. These results suggest that the decision to hedge was profitable for the company. And at the same time the company’s obligation under Indonesian central bank’s regulation to conduct hedging could also be fulfilled. The recommendation that can be given to management is that a company should continue to conduct hedging through the forward contract in the future to minimize the transaction exposure of foreign currency due to its volatility.